The effects of risk management on management forecast behavior - Campbell, John L. (Institutional Knowledge at Singapore Management University, 2017)
Prior research examines several reasons why managers voluntarily disclose information, but provides relatively little evidence as to whether day-to-day operational decisions influence a manager’s disclosure choice. In this study, we examine whether a particular operational activity – risk management through the use of derivatives – affects whether a manager decides to issue earnings forecasts. Using a large hand-collected sample of derivatives users and non-users, we find that derivatives users are more likely to issue earnings forecasts relative to non-users. We then find that this result is stronger when the use of derivatives makes it less costly for managers to issue forecasts and to meet or beat those forecasted earnings. Interestingly, however, we find no evidence that managers provide these forecasts when investors are more likely to demand them. Overall, our results suggest that operational decisions can influence management forecast policy, but only when these decisions make it easier for the managers to predict future earnings. This study thus provides evidence that voluntary disclosure has a role, but with limitation, in helping investors understand the complexity of derivatives.